Why are Children Still Working? - Heri Sandra; Taufiq Carnegie Dawood; M. Shabri Abd. Majid (Jurnal Ekonomi dan Studi Pembangunan, 2022)
This study aims to determine the effect of household characteristics and children's living environment on child labor to reduce the likelihood of child labor occurrence. The data source of this research is Sakernas (Indonesian National Labor Force Survey) of August 2018, including school accreditation, household head gender, age, working sector, employment status, household size, dependency ratio, location, and school quality, towards the probability of child labor occurrence in Indonesia. Results suggest that the government must prioritize welfare programs for women household heads, asses the minimum age for marriage, improve education facilities, and increase parental awareness to eliminate child labor. The government needs to improve education infrastructure. This infrastructure improvement should be accompanied by the convenience of school access and its costs. The lack of education infrastructure, especialy in rural areas makes it difficult for children there to attend formal schooling.